2002
DOI: 10.1046/j.1365-2184.2002.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of cytoplasmic HSP70 onto the surface of EL‐4 cells during apoptosis

Abstract: Heat shock proteins (HSPs) are involved in a variety of intracellular processes and can have both pro- and anti-apoptotic action. However, little is known about the role of HSPs in the progression of apoptosis. Translocation of HSPs to the surface of apoptotic cells is a previously observed phenomenon demonstrating participation of these proteins in execution of the terminal stages of apoptosis. In a previous study we showed that development of EL-4 lymphoma cell apoptosis in vitro is accompanied by elevation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Originally, HSPs were known to play an important role in chaperoning by transiently associating with nascent polypeptides to facilitate correct folding in the cytoplasm and nucleus [35]. However, recently it has been demonstrated that HSP70 does occur on the surface of a number of cell types [25,26,[36][37][38][39][40][41][42]. In most studies, the extracellular presence of HSP70 was considered to be the outcome of necrotic or apoptotic cell death of neighboring cells, but recent evidence strongly supports active release of HSP70s from cells in response to stresses, including cytokines, acute psychological stress, and exercise [43,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, HSPs were known to play an important role in chaperoning by transiently associating with nascent polypeptides to facilitate correct folding in the cytoplasm and nucleus [35]. However, recently it has been demonstrated that HSP70 does occur on the surface of a number of cell types [25,26,[36][37][38][39][40][41][42]. In most studies, the extracellular presence of HSP70 was considered to be the outcome of necrotic or apoptotic cell death of neighboring cells, but recent evidence strongly supports active release of HSP70s from cells in response to stresses, including cytokines, acute psychological stress, and exercise [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…As HSP70 was expressed on the surface of several cancer cell lines [25,26,[36][37][38][39][40][41][42], we examined the surface expression of the HSPA8 protein in some cancer cell lines by flow cytometry. As in Miz-hES1, we could observe its surface expression in Choi-CK, SH-J1, and HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…been demonstrated that HSP70 does occur on the surface of a number of cell types (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). However, our ability to comprehensively profile cell surface proteins has uncovered the high abundance of heat-shock proteins compared with other cell surface proteins.…”
Section: Figmentioning
confidence: 99%
“…Although Hsp70 expression by PMN requires de novo protein synthesis and the transport of the protein to the cell surface (7), the question of whether this mechanism is universal for surface expression of Hsp in other cells as well remains to be investigated. Several studies have shown that cells can externalize Hsp molecules during apoptotic transformation (23)(24)(25). Another possible mechanism is through the binding of Hsp molecules that are produced by other cells.…”
Section: Hsp and Cellular Distressmentioning
confidence: 99%